Successful treatment of an intrahepatic congenital portosystemic shunt causing dysfunction in a pediatric liver transplant graft - Siobhan Flanagan, MD; Allison Aguado, MD; Srinath Chinnakotla, MD, MCh (Radiology Case Reports)
A 5-month-old child developed severe liver dysfunction after a liver transplant with a partial liver graft. Ultrasound examination revealed a communication between the left portal vein and the left hepatic vein, a rare congenital portosystemic shunt. Here we describe the successful management of this shunt with an endovascular closure device. Prompt recognition of the shunt and use of the closure device to occlude the shunt can result in an excellent outcome.